Optimal energy storage configuration for joint energy‐regulation market participating renewable energy plants with excess revenue recovery mechanism - Weihong Liu; Qiangyu Ren; Jiaojiao Deng; Jincheng Guo; Xiaoming Zheng; Hongli Liu (IET Energy Systems Integration, 2023)
Abstract The fluctuation and stochastic characteristics of renewable energy resources challenge the secure system operation and also impose significant financial risks for the market participating renewable energy plants (REPs). Energy storage systems (ESSs) can serve as effective tools in enhancing the operating flexibility of REPs, thus improving their profitability while making them grid‐friendly. However, current studies focussing on the energy market participation of ESS‐equipped REPs neglect ESSs' frequency regulation performance. Moreover, power output deviation and power curtailment of REPs bring difficulties to the integration of renewable energy. To address these challenges, an optimal ESS configuration method for REPs participating in the joint energy‐regulation market is proposed first. A method considering constraints on frequency regulation performance is applied. Then, to reduce power output deviation and power curtailment of REPs, an incentive mechanism based on the excess revenue recovery is implemented to induce the grid‐friendly power outputs of REPs. Numerical analysis on XJTU‐ROTS2017 systems demonstrates that the optimal ESS configuration results obtained from the proposed method could promote the profitability of ESS‐equipped REPs. The results also verify the effectiveness of the excess revenue recovery mechanism in facilitating the grid‐friendly operation behaviours of the ESS‐equipped REPs.